Centering the Bayan Youth of Lombok: Local-Based Religious Cultural Tourism Development in Indonesia - Misbah Zulfa Elizabeth; Ririh Megah Safitri; Naili Ni'matul Iliyyun; Akhriyadi Sofian; Endang Supriadi; Luksi Visita (Al-Albab, 2025)
Tourism development strategies are an important aspect of tourism development. Bayan Mosque in Lombok is important to develop as religious cultural tourism using a local approach. Applying qualitative methods, case study approach and field research this study aims to uncover the problems faced by the local community in developing cultural tourism; the local community has done to overcome these problems; the impact these efforts have had on the development of Bayan cultural tourism. The study revealed that the problems faced by the local community in developing Bayan religious cultural tourism include a lack of awareness among the local community regarding the potential of Bayan Mosque as a tourist destination, the absence of any institution managing the potential of the tourist destination; insufficient government attention to designing integrated cultural tourism within the community, and the scope of development efforts remains limited. Some young people in Bayan have made efforts such as supporting the emergence of local identity; developing visits to traditional villages around the Bayan Mosque; hearings with the Tourism Office for possible assistance; forming a youth group that promotes tourism awareness; and involving the media in major events at the Bayan Mosque. The impact of these efforts has already led to a significant increase in tourist visits to the Bayan Mosque. These increasing visits are related to the efforts of the local community to involve the media in attracting tourists. It can be concluded that efforts to develop tourism must be comprehensive, including the media.